(untitled) (Italian Journal of Public Health, 2005)
Background. Benzodiazepines are among the most commonly prescribed drugs in Italy and they are often used inappropriately according to guidelines for their rational use. The aim of this study was to investigate the prevalence and pattern of use of benzodiazepine amongst the general population aged 65-84 years in the Friuli-Venezia Giulia Region, in North-East Italy. Methods. A total of 40 general practitioners participated in the study. Two data sources were used in the research. The first was the Health Search Database, the second was a short questionnaire administered by the general practitioners to the 65 to 84 year old patients attending their surgeries for any reason during the study period. Data on the use of benzodiazepines between 1st February and 31st July 2001 were extracted from both the Health Search Database using drug prescriptions and the questionnaires. Results. Of the 10,468 patients aged 65-84 years with complete demographical data in the general practitioners’ patient lists, 2,369 subjects used benzodiazepines, hypnotics and over the counter drugs. Overall prevalence of benzodiazepine use was 21.5% (95% confidence interval: 19.8-23.1%). Of the benzodiazepine users, 66.9% consumed a short-intermediate half-life and 33.1% a long half-life benzodiazepine. Most patients took benzodiazepines at night (68.2%), less frequently in the daytime and at night (23.7%), or in the daytime only (8.1%). Most users (89.2%) said they had been taking benzodiazepine for years. Conclusions. Benzodiazepine use was associated with patient characteristics, such as being female, using analgesics or antidepressants and the presence of a chronic disease especially cancer or chronic heart failure.